Flux, gaugino condensation, and antibranes in heterotic M theory - Gray, J; Lukas, A; Ovrut, B (2007)
We present the potential energy due to flux and gaugino condensation in heterotic M theory compactifications with antibranes in the vacuum. For reasons which we explain in detail, the contributions to the potential due to flux are not modified from those in supersymmetric contexts. The discussion of gaugino condensation is, however, changed by the presence of antibranes. We show how a careful microscopic analysis of the system allows us to use standard results in supersymmetric gauge theory in describing such effects-despite the explicit supersymmetry breaking which is present. Not surprisingly, the significant effect of antibranes on the threshold corrections to the gauge kinetic functions greatly alters the potential energy terms arising from gaugino condensation. © 2007 The American Physical Society.